Electronic Voting Research Papers in Web of Science: A Bibliometric Analysis - Singh Reen, Tarandeep; Gochhait, Saikat (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The main aim of the paper is to investigate and recognize trends in electronic voting research at an international level.Design/methodology/approach: Retrieval of the data was from the database of Web of Science on the topic Electronic Voting that covered the period from 1988-2020 to identify useful contributions that have been produced and published in the respective field. A total of 994 data records were retrieved from the database. Several trends predominating in digital voting research, including well-known contributing countries, adopted patterns of authorship, the degree of co-authorship, cross-country co-authorship, prominent sources for research publication, recognition of research in the course of citation trends like average citation per year, top-cited papers, citations received/citations per paper, etc., were discovered by analysis of the data.Findings: There has been constructive growth in the literature since 1988, as revealed by the analysis. As evident from the analysis, half of the research output was contributed by the five countries—USA, England, China, Spain, and Germany—with a total of 491 journals published. When it comes to the effectiveness of the papers, Denmark leads with a PEI of 4.87. It is followed by Canada with a PEI of 4.60 and Scotland with a PEI of 2.80.Most of the journals belong to the Computer Science and Political Science categories of Web of Science.Also, the number of times these papers are cited per year is increasing rapidly for the given duration. This shows there is an increase in research in the field of digital voting. The COVID-19 pandemic can be held accountable for the irregularity in the trend in 2020 that has halted the research in the field. On performing linear regression, it was observed that we can expect positive growth in the number of citations in the coming years.